Thermoplastic starch composition containing halogenated metal salt, pellets, flakes, compounded body, resin molded article, method for producing thermoplastic starch composition, method for producing pellets or flakes, method for producing compounded body, and method for producing resin molded article

By adding metal halide salt to the thermoplastic starch composition and molding under specific conditions, the problems of poor fluidity and easy discoloration of the composition are solved, high fluidity and low discoloration characteristics are achieved, and the performance of the finished product is improved.

JP2025063735AActive Publication Date: 2025-04-16NIHON SHOKUHIN KAKO CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023173164
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-04
Publication Date
2025-04-16
Estimated Expiration
2043-10-04

AI Technical Summary

Technical Problem

The conventional thermoplastic starch compositions are prone to discoloration when using starch plasticizer, and have poor fluidity without metal halide salts, resulting in difficulty in uniform dispersion in the thermoplastic resin, affecting the physical properties of the finished resin product.

Method used

High flowability and low discoloration properties of the composition are ensured by adding starch, starch plasticizers and metal halide salts to the thermoplastic starch composition and mixing and forming at specific temperatures and pressures.

Benefits of technology

The high flowability and low discoloration characteristics of the thermoplastic starch composition are achieved, the dispersion and finished product performance in the thermoplastic resin are improved, and the problems of poor flowability and easy discoloration of the composition in the prior art are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025063735000012
    Figure 2025063735000012
  • Figure 2025063735000001
    Figure 2025063735000001
  • Figure 2025063735000002
    Figure 2025063735000002
Patent Text Reader

Abstract

To provide a thermoplastic starch composition that is resistant to discoloration and exhibits fluidity.SOLUTION: A thermoplastic starch composition according to the present disclosure comprises starch, a plasticizer for starch, and a halogenated metal salt, and has a melt flow rate of 0.01 g / 10 min or more at a temperature of 160°C under a load of 5 kg as determined in accordance with JIS K7210.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to thermoplastic starch compositions, pellets, flakes, compound bodies, resin molded articles, methods for producing thermoplastic starch compositions, methods for producing pellets or flakes, methods for producing compound bodies, and methods for producing resin molded articles. [Background technology]

[0002] Recently, from the viewpoints of utilizing renewable materials and reducing carbon dioxide emissions, i.e., carbon circulation, and protecting the global environment through the widespread use of biodegradable resins, there is a demand to switch from conventional petroleum-derived resins to biomass-derived resins. In this context, Patent Documents 1 and 2 disclose a method of blending starch into a resin. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2011-026538 A [Patent Document 2] Special Publication No. 2011-522950 Summary of the Invention [Problem to be solved by the invention]

[0004] Here, as in Patent Document 1, when a starch plasticizer is used to plasticize starch, the compound body may become discolored. Also, as in Patent Document 2, a composition in which starch is simply mixed with a starch plasticizer may have significantly low fluidity. A composition with low fluidity is difficult to disperse in a thermoplastic resin, which may cause a decrease in the physical properties of a resin molded product. A resin molded product manufactured using such a compound body or composition has limited physical properties and quality, which inevitably limits its applications.

[0005] Therefore, an object of the present disclosure is to provide a thermoplastic starch composition having little coloration and fluidity, a pellet, a flake, a compound body, a resin molding, a method for producing a thermoplastic starch composition, a method for producing pellets or flakes, a method for producing a compound body, and a method for producing a resin molding. [Means for solving the problem]

[0006] In order to achieve the above object, one embodiment of the thermoplastic starch composition of the present disclosure comprises: The present invention comprises a starch, a plasticizer for starch, and a metal halide salt, The thermoplastic starch composition has a melt flow rate of 0.01 g / 10 min or more at a temperature of 160° C. under a load of 5 kg according to JIS K 7210.

[0007] One aspect of the thermoplastic starch composition of the present disclosure comprises: The present invention comprises a starch, a plasticizer for starch, and a metal halide salt, A thermoplastic starch composition, wherein the thermoplastic starch composition formed into pellets has a whiteness change rate X of 40% or less, as calculated by the following formula (1): X = {(AB) / A} × 100 (1) In the formula (1), A is the whiteness (WB) of the thermoplastic starch composition after molding, calculated in accordance with JIS Z8715; B is the whiteness (WB) of the thermoplastic starch composition after the molding is heated at 160° C. for 30 minutes, calculated in accordance with JIS Z8715.

[0008] The pellets of the present disclosure comprise the thermoplastic starch composition of the present disclosure.

[0009] The flakes of the present disclosure comprise the thermoplastic starch composition of the present disclosure.

[0010] The compound body of the present disclosure comprises the thermoplastic starch composition of the present disclosure.

[0011] The resin molded article of the present disclosure comprises the thermoplastic starch composition of the present disclosure.

[0012] The method for producing the thermoplastic starch composition of the present disclosure includes: The method includes a mixing step of mixing raw materials containing the starch, the plasticizer for starch, and the metal halide salt.

[0013] The method of making pellets or flakes of the present disclosure includes: a strand forming step of extruding the thermoplastic starch composition to form strands; and a strand cutting step of cutting the strands to form pellets or flakes, The thermoplastic starch composition is the thermoplastic starch composition of the present disclosure.

[0014] The method for producing the compound body of the present disclosure includes: A first kneading step of kneading a raw material containing pellets or flakes and a raw material containing a thermoplastic resin, The pellets are pellets of the present disclosure, The flakes are flakes of the present disclosure.

[0015] The method for producing a resin molded product according to the present disclosure includes: A resin molding process is included in which a raw material including a compound body is resin-molded to produce a resin molded product, The compound body is a compound body of the present disclosure. Effect of the Invention

[0016] According to the present disclosure, a thermoplastic starch composition having little coloration and good fluidity can be obtained. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 shows photographs of the thermoplastic starch compositions of test plots A-2, X-1, and X-2 before and after heating. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Preferred embodiments for carrying out the present disclosure will be disclosed below. However, the following embodiments disclose representative embodiments of the present disclosure, and the scope of the present disclosure is not limited to these embodiments.

[0019] In the present disclosure, unless otherwise specified, "mass %" and "weight %" may be read interchangeably, and "parts by mass" and "parts by weight" may be read interchangeably.

[0020] In the present disclosure, unless otherwise specified, the term "strand" refers to a general term for a thermoplastic starch composition extruded from various extruders, and the shape such as length is not particularly limited. For example, it includes any shape extruded from various extruders, such as a long string-like one or a short plate-like one.

[0021] <Thermoplastic starch composition> First, the thermoplastic starch composition of the present disclosure will be described.

[0022] [Melt flow rate (MFR)] In one embodiment of the present disclosure, the melt flow rate (MFR) of the thermoplastic starch composition at a temperature of 160° C. and a load of 5 kg according to JIS K 7210 is 0.01 g / 10 min or more. The lower limit of the MFR may be, for example, 0.05 g / 10 min or more, 0.1 g / 10 min or more, or 0.2 g / 10 min or more, and the upper limit may be, for example, 100 g / 10 min or less, 80 g / 10 min or less, or 65 g / 10 min or less. The MFR can be measured by a measurement method described in the Examples below. The MFR can be adjusted, for example, by adjusting the compounding ratio of starch, compatibilizer, thermoplastic resin, starch plasticizer, or metal halide salt, or the like, or the production conditions during production, such as the production temperature or kneading time, which will be described later.

[0023] When the MFR of the thermoplastic starch composition of the present disclosure is 0.01 g / 10 min or more, a thermoplastic starch composition exhibiting high fluidity can be obtained. For example, the present disclosure is useful when a compound body having a high starch content and a high breaking elongation value is desired. Note that when the starch content is increased, a compound body containing a thermoplastic starch composition with a low MFR tends to have a lower breaking elongation.

[0024] [Whiteness change rate] In one embodiment of the present disclosure, the thermoplastic starch composition has a whiteness change rate X of 40% or less when the thermoplastic starch composition is molded into a pellet, as calculated by the following formula (1). The whiteness change rate X may be, for example, 40% or less, 35% or less, 30% or less, 25% or less, 20% or less, or 10% or less, or may be 0% or more, 1% or more, 2% or more, 3% or more, 4% or more, or 5% or more. X = {(AB) / A} × 100 (1) In the formula (1), A is the whiteness (WB) of the thermoplastic starch composition after molding, calculated in accordance with JIS Z8715; B is the whiteness (WB) of the thermoplastic starch composition after the molding is heated at 160° C. for 30 minutes, calculated in accordance with JIS Z8715.

[0025] In the present disclosure, the thermoplastic starch composition is the thermoplastic starch composition not containing a metal halide salt described below, a and the whiteness change rate X of a thermoplastic starch composition in which a part of a starch plasticizer described below contained in the thermoplastic starch composition not containing a metal halide salt is replaced with a metal halide salt. b , and the difference (X a -X b ) may be, for example, 100 or less, 70 or less, or 50 or less, or 1 or more, 3 or more, or 5 or more. a and the whiteness change rate X bcan be calculated by the above formula (1).

[0026] In addition, when a compound body or a resin molded product described later is manufactured using a thermoplastic starch composition having a high whiteness change rate, the whiteness (WB) of the compound body and the resin molded product is also reduced. That is, the manufactured compound body and the resin molded product are colored. Therefore, it is preferable that the whiteness change rate X of the thermoplastic starch composition is as small as possible.

[0027] [Biomass ratio] The biomass degree Y of the thermoplastic starch composition of the present disclosure is calculated, for example, by the following formula (2): The biomass degree Y is, for example, 80% or more, preferably 90% or more, most preferably 95% or more, 96% or more, 97% or more, 98% or more, or 99% or more, and is less than 100%, preferably 99.9% or less, 99.8% or less, 99.7% or less, or 99.6% or less, and most preferably 99.5% or less. Y = (C / D) × 100 (2) In the formula (2), C is the weight of biomass-derived material in the thermoplastic starch composition; D is the total weight of the thermoplastic starch composition.

[0028] [starch] The starch is not particularly limited, and examples thereof include unmodified starches obtained from corn, potato, sweet potato, cassava, sago palm, rice, wheat, etc. That is, examples thereof include corn starch, waxy corn starch, high amylose corn starch, potato starch, sweet potato starch, tapioca starch, sago starch, rice starch, wheat starch, etc. In addition, examples thereof include processed starches obtained by etherifying or esterifying unmodified starch, or by subjecting the starch to a crosslinking treatment, etc. The starch may be used alone or in combination of two or more kinds.

[0029] The starch is preferably, for example, cornstarch or tapioca starch, which is an unprocessed starch, from the viewpoint of production cost, and more preferably cornstarch. As described above, it is presumed that the low molecular weight material exhibits coloration and thermal decomposition when heated due to an increase in the number of reducing ends, and in this respect, cornstarch or tapioca starch, which is an unprocessed starch, is also preferable. In general, cornstarch is the most preferable.

[0030] The moisture content of the starch used in the present disclosure is not particularly limited, but is, for example, 5 to 25% by weight, more preferably 7 to 23% by weight, even more preferably 9 to 20% by weight, and most preferably 10 to 18% by weight.

[0031] The content of the starch is, for example, 55% by weight or more, more preferably 60% by weight or more, and even more preferably 65% ​​by weight or more, based on 100% by weight of the total weight of all components other than water contained in the thermoplastic starch composition, in consideration of improving the biomass ratio, and 85% by weight or less, more preferably 80% by weight or less, and most preferably 75% by weight or less, based on 100% by weight of the total weight of all components other than water contained in the thermoplastic starch composition, in consideration of mixing with a thermoplastic resin, and the range is, for example, 55 to 85% by weight, more preferably 60 to 85% by weight, even more preferably 60 to 80% by weight, and most preferably 65 to 75% by weight. In the present disclosure, even if the content of starch is as high as 55 parts by weight or more, it exhibits high fluidity as long as the MFR is 0.01 g / 10 min or more, and can be easily kneaded with a thermoplastic resin or the like.

[0032] The starch may be, for example, non-oxidized starch. In the present disclosure, the term "non-oxidized starch" refers to starch that is not oxidized starch, unless otherwise specified. The oxidized starch is a general term for starch in which, for example, aldehyde reducing groups, hydroxyl groups, glycol groups, etc. present in starch are oxidized to carboxyl groups or carbonyl groups by an oxidizing agent such as chlorine, bromine, hypochlorite, hypobromite, etc., or are hydrolyzed in association with an oxidation reaction, thereby reducing the molecular weight. In addition, starch that has been subjected to other chemical treatments, such as acetylated oxidized starch, is also included in the oxidized starch. As described in the examples below, if the content of oxidized starch in the present disclosure is too high, the whiteness change rate of the thermoplastic starch composition tends to be high. Therefore, the content of the oxidized starch is preferably within the range described below. On the other hand, for example, starch that is substantially not oxidized by acting a very small amount of the oxidizing agent on starch is considered to be non-oxidized starch in the present disclosure if the whiteness change rate is low.

[0033] The thermoplastic starch composition of the present disclosure may or may not contain the oxidized starch as an optional component in addition to the non-oxidized starch. The oxidized starch is, for example, starch oxidized by an oxidizing agent, more specifically, starch oxidized by chlorine, starch oxidized by bromine, starch oxidized by hypochlorite, starch oxidized by hypobromite, etc. When the oxidized starch is contained, the content of the oxidized starch is preferably more than 0 wt%, 25 wt% or less, 20 wt% or less, or 10 wt% or less, based on the total weight of all components other than water contained in the thermoplastic starch composition being 100 wt%, from the viewpoint of reducing the production cost of the thermoplastic starch composition of the present disclosure and the viewpoint of reducing the whiteness change rate.

[0034] In addition, since the oxidized starch may be discolored or easily thermally decomposed when heated due to an increase in the number of reducing ends and an increase in aldehyde groups resulting from an oxidation reaction, it is preferable to set the content at the above-mentioned level.

[0035] [Metal halide salts] The metal halide salt used in the present disclosure may be, for example, a known metal halide salt. The metal halide salt may include, for example, at least one selected from the group consisting of metal chloride salts, metal bromide salts, and metal iodide salts. The effect of imparting fluidity to the thermoplastic starch composition described below depends, for example, on the amount of the metal halide salt contained in the thermoplastic starch composition. The greater the amount of the metal halide salt contained in the thermoplastic starch composition, the greater the effect of imparting fluidity described above. Therefore, the metal halide salt preferably includes at least one of a metal chloride salt and a metal bromide salt, which includes more molecules (i.e., has a smaller molar mass) even with the same weight of the metal halide salt, and more preferably includes a metal chloride salt. The metal halide salt may be, for example, at least one selected from the group consisting of sodium chloride, magnesium chloride, calcium chloride, aluminum chloride, sodium bromide, magnesium bromide, calcium bromide, sodium iodide, magnesium iodide, and calcium iodide.

[0036] The form of the metal halide salt is not particularly limited, and may be, for example, a solid such as a powder, or a liquid such as an aqueous solution. From the viewpoint of dispersion in the starch, which is the raw material, the liquid form is preferred.

[0037] The content of the metal halide salt is, for example, 0.1 to 10% by weight, more preferably 0.2 to 8% by weight, even more preferably 0.25 to 7% by weight, and most preferably 0.3 to 5% by weight. The content of the metal halide salt is preferably 0.1% by weight or more from the viewpoint of increasing the starch content, and is preferably 10% by weight or less from the viewpoint of imparting an effect of improving coloring.

[0038] Here, a thermoplastic starch composition that does not contain the metal halide salt, for example, a thermoplastic starch composition produced by mixing the starch with the starch plasticizer, particularly one with a high starch content of 50% by weight or more, has low fluidity (MFR). Therefore, it is difficult to disperse the starch when kneaded with a thermoplastic resin described later, and it is presumed that this causes a decrease in the physical properties of the compound body. On the other hand, the inventors of the present disclosure have found that the fluidity of the thermoplastic starch composition is greatly improved by mixing a mixture containing the starch, the starch plasticizer, and the metal halide salt under heating. From this, it is presumed that the metal halide salt imparts high fluidity to the thermoplastic starch composition by plasticizing the starch or changing the structure of the starch. However, this is merely a hypothesis, and the present disclosure is not limited thereto.

[0039] [Starch plasticizer] In the present disclosure, unless otherwise specified, the term "starch plasticizer" refers to a plasticizer used to plasticize starch, and does not refer to a plasticizer that is generally used by those skilled in the art in a starch-free form to adjust the physical properties of a thermoplastic resin.

[0040] The starch plasticizer is not particularly limited as long as it is a substance that substantially plasticizes the starch, except for water, and examples thereof include polyhydric alcohols, sugars, ammonia, ureas, ionic liquids, etc. Examples of the polyhydric alcohols include glycerol (glycerin), ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-heptanediol, 1,6-hexanediol, 1,8-octanediol, 1,9-nanonediol, 1,10-decanediol, 1,12-dodecanediol, diethylene glycol, triethylene glycol, polyethylene glycol, dipropylene glycol, tripropylene glycol, polypropylene glycol, diglycerol, etc. Examples of the sugars include sorbitol, glucose, maltitol, mannitol, erythritol, etc. These may be used alone or in combination of two or more. These substances may be, for example, pre-contained in the starch. In addition, when a thermoplastic resin described later is contained, the thermoplastic resin may be pre-contained. Furthermore, the substance may be contained at any timing when the thermoplastic starch composition of the present disclosure is obtained.

[0041] From the viewpoint of the effect of plasticizing starch, the starch plasticizer used in the present disclosure is preferably glycerin, propylene glycol, or sorbitol, and more preferably glycerin.

[0042] The content of the starch plasticizer is, for example, 5 to 40% by weight, more preferably 10 to 35% by weight, even more preferably 15 to 30% by weight, and most preferably 20 to 30% by weight, relative to 100% by weight of the total weight of all components other than water contained in the thermoplastic starch composition.

[0043] In addition, it is preferable that the starch plasticizer does not substantially contain water. In other words, it is preferable that the starch plasticizer is, for example, a starch plasticizer that does not contain water as a main component. This is because, for example, when water is used as the main component of the starch plasticizer, foaming occurs due to evaporation of water during the production of the thermoplastic starch composition or during the molding of a compound body described later. For example, when the thermoplastic starch composition is produced using an extruder, if the thermoplastic starch composition unintentionally foams at the outlet of the extruder, productivity may decrease. In addition, during the normal production of the thermoplastic starch composition or during the molding of a compound body described later, high temperature conditions of 100°C or higher and removal of gas by vacuum deaeration are involved, so that plasticizers with low boiling points such as water are more likely to be discharged outside the system. As a result, the starch plasticizer component contained in the thermoplastic starch composition before forming the strands is reduced compared to before the kneading, the thermoplasticity of starch is lost, and the dispersibility of the starch in the thermoplastic starch composition may be significantly reduced.

[0044] [Thermoplastic resin] The thermoplastic starch composition of the present disclosure may or may not further include a thermoplastic resin. In addition, as described later, the thermoplastic starch composition of the present disclosure and the thermoplastic resin may be kneaded to obtain a compound. The thermoplastic resin is not particularly limited, and for example, a general known thermoplastic resin may be used. In addition, for example, a thermoplastic resin having biodegradability may be used. For example, polyolefin-based resins that are polymers of olefins having 2 to 20 carbon atoms, such as polypropylene, polybutene, polypentene, and polyethylene; polycyclic olefin-based resins such as polynorbornene; polystyrene-based resins such as polystyrene and ABS resin; polyester-based resins such as polylactic acid, polyethylene terephthalate, polybutylene terephthalate, and polybutylene succinate, and mixtures thereof may be used. Examples of the polyethylene include linear low-density polyethylene, low-density polyethylene, very low-density polyethylene, medium-density polyethylene, and high-density polyethylene. Also, it may be a copolymer, and examples thereof include ethylene-propylene (block and random) copolymers, ethylene-α-olefin (α-olefin having 4 to 20 carbon atoms) copolymers, propylene-α-olefin (α-olefin having 4 to 20 carbon atoms) copolymers, ethylene-vinyl acetate copolymers, ethylene-acrylic acid copolymers, etc. The thermoplastic resins may be used alone or in combination of two or more kinds.

[0045] The thermoplastic resin is preferably, for example, polyethylene or polypropylene from the viewpoint of versatility, and more preferably polyethylene.

[0046] The melt flow rate of the thermoplastic resin may be, for example, 0.1 g / 10 min or more, 2 g / 10 min or more, or 5 g / 10 min or more from the viewpoint of production speed, and may be 70 g / 10 min or less, 60 g / 10 min or less, or 40 g / 10 min or less, and the range is, for example, preferably 0.1 to 70 g / 10 min, 2 to 70 g / 10 min, or 5 to 60 g / 10 min, and more preferably 5 to 40 g / 10 min. The melt flow rate may be determined, for example, by the method described in JIS K 7210 using a melt indexer, or may be data described in literature, etc.

[0047] The content of the thermoplastic resin is not particularly limited, but in consideration of improving the biomass degree, it is preferable to have a high content of the starch, for example, 0% by weight. In addition, when the thermoplastic resin is contained, the total weight of all components other than water contained in the thermoplastic starch composition is taken as 100% by weight, and for example, the lower limit is more than 0% by weight, and the upper limit is 30% by weight or less, more preferably 20% by weight or less, even more preferably 10% by weight or less, and most preferably 5% by weight or less.

[0048] [Compatibilizer] The thermoplastic starch composition of the present disclosure may or may not further include a compatibilizer. The compatibilizer is not particularly limited, and may be, for example, a general known compatibilizer. For example, the compatibilizer may include one or more selected from the group consisting of compounds having an acid anhydride group such as maleic anhydride, succinic anhydride, and glutaric anhydride, compounds having a carboxyl group such as maleic acid, succinic acid, and glutaric acid, compounds having an epoxy group, compounds having an imino group, compounds having an isocyanate group, compounds having an oxazoline group, and compounds having a reactive group such as an alkoxy group, such as a silane coupling agent. The acid anhydride group, the epoxy group, the imino group, and the isocyanate group are functional groups that can react with a hydroxy group, and compounds having such functional groups are preferred as the compatibilizer of the present disclosure. Examples of the compound that can be used as the compatibilizer include polymer compounds having the above-mentioned functional groups such as polyolefin-based, acrylic-based, and styrene-based polymer compounds, and polyolefin-based polymer compounds having the above-mentioned functional groups are preferred from the viewpoint of ensuring affinity with the resin to be blended.

[0049] Examples of the polyolefin polymer compound include ethylene polymers [high density polyethylene, medium density polyethylene, low density polyethylene, copolymers of ethylene and one or more vinyl compounds (e.g., α-olefin, vinyl acetate, methacrylic acid, acrylic acid, etc.)], propylene polymers [polypropylene, copolymers of propylene and one or more vinyl compounds], ethylene-propylene copolymers, polybutene, and poly-4-methylpentene-1, etc., and preferably propylene polymers. Specific examples of the polyolefin polymer compound having the functional group as described above include maleic anhydride modified polyolefins, more specifically maleic anhydride modified polypropylenes.

[0050] When the thermoplastic starch composition of the present disclosure contains a compatibilizer, the content of the compatibilizer is, for example, 0.1 to 10% by weight, where the total weight of all components other than water contained in the thermoplastic starch composition is taken as 100% by weight. The content of the compatibilizer may be, for example, a lower limit of 0.1% by weight or more, 0.5% by weight or more, or 1% by weight or more, and an upper limit of 10% by weight or less, 8% by weight or less, and the range is, for example, preferably 0.1 to 10% by weight, more preferably 0.1 to 8% by weight, even more preferably 0.5 to 8% by weight, and most preferably 1 to 8% by weight, where the total weight of all components other than water contained in the thermoplastic starch composition is taken as 100% by weight.

[0051] [Other additives] The thermoplastic starch composition of the present disclosure may or may not further contain various additives known in the art. Examples of the additives include emulsifiers, elastomers, inorganic fillers, heat stabilizers, light resistance agents, ultraviolet absorbers, antistatic agents, and the like. These may be used alone or in combination of two or more. Furthermore, these substances may be, for example, pre-contained in the starch. Furthermore, in the case where a thermoplastic resin described later is contained, these substances may be pre-contained in the thermoplastic resin. Furthermore, they may be contained at any timing when the thermoplastic starch composition of the present disclosure is obtained.

[0052] [Water contained in thermoplastic starch composition] As described above, in the thermoplastic starch composition of the present disclosure, it is preferable that the starch plasticizer does not substantially contain water. This is because, as described above, when the thermoplastic starch composition containing water substantially contains water as the starch plasticizer, the water contained as the starch plasticizer is likely to be discharged outside the system when the thermoplastic starch composition containing water is kneaded (heated). As a result, the starch plasticizer component contained in the thermoplastic starch composition before forming into strands is reduced in weight compared to before the kneading, the thermoplasticity of the starch is lost, and the dispersibility of the starch in the thermoplastic starch composition may be significantly reduced.

[0053] On the other hand, when the content of the starch plasticizer satisfies the above-mentioned numerical range (hereinafter, sometimes simply referred to as "when the starch plasticizer is sufficiently contained"), the thermoplastic starch composition of the present disclosure may contain a small amount of water. When the starch plasticizer is sufficiently contained, it is preferable that the thermoplastic starch composition of the present disclosure contains a small amount of water (i.e., when the water content exceeds 0 mass%), because the plasticization of the thermoplastic starch composition is easily promoted and the production conditions of the thermoplastic starch composition can be easily optimized. In the case where the starch plasticizer is sufficiently contained, the moisture content contained in all the raw materials constituting the thermoplastic starch composition of the present disclosure (hereinafter, sometimes simply referred to as "total moisture content of raw materials") is, for example, more than 0% by weight and 30% by weight or less, preferably 5 to 30% by weight, more preferably 6 to 25% by weight, even more preferably 7 to 22% by weight, and most preferably 8 to 20% by weight, taking the total weight of all components other than water contained in the thermoplastic starch composition as 100% by weight, in consideration of the dispersibility of the metal halide salt and the plasticity of the starch. The total moisture content of raw materials in the present disclosure may be calculated, for example, from the ratio of the weight of water added to the thermoplastic starch composition and the total moisture content of all components other than water contained in the thermoplastic starch composition to the total weight of the thermoplastic starch composition. In addition, the total moisture content of raw materials in the present disclosure may be calculated, for example, from the weight change before and after drying of the thermoplastic starch composition dried by a dryer or the like, or may be measured using a device such as a moisture meter.

[0054] The thermoplastic starch composition provided in the present disclosure is not limited in its final form, and may be in the form of, for example, pellets or flakes described below, a compound body obtained by further mixing the pellets or flakes with a thermoplastic resin, a resin molded product obtained by further mixing the compound body with another thermoplastic resin, or a resin molded product obtained by molding them, which will be described later.

[0055] <Pellets, flakes, compounds, and resin molded products> Next, the pellets, flakes, compound bodies, and resin molded products of the present disclosure will be described.

[0056] As described above, the pellets and flakes of the present disclosure include the thermoplastic starch composition of the present disclosure. In the present disclosure, the term "pellets" refers to, for example, the thermoplastic starch composition molded into a granular shape or the like, and more specifically, refers to a molded product obtained by cutting the thermoplastic starch composition in the form of strands. In addition, the term "pellet-like" refers to the shape or form of the product obtained when the thermoplastic starch composition in the form of strands is cut into a granular shape or the like. In the present disclosure, the term "flakes" refers to, for example, the thermoplastic starch composition molded into a plate, cube, rectangular parallelepiped, polygonal prism, polygonal pyramid, or the like, and more specifically, refers to a molded product obtained by cutting the thermoplastic starch composition in the form of strands. In addition, the term "flake-like" refers to the shape or form of the product obtained when the thermoplastic starch composition in the form of strands is cut into a plate, cube, rectangular parallelepiped, polygonal prism, polygonal pyramid, or the like.

[0057] As described above, the compound body of the present disclosure contains the thermoplastic starch composition of the present disclosure and another thermoplastic resin. The other thermoplastic resin is not particularly limited, and may be, for example, the same as the thermoplastic resin described in the thermoplastic starch composition of the present disclosure. The compound body of the present disclosure may be extrusion molded and molded again into pellets, flakes, sheets, etc. The compound body molded into pellets, flakes, etc. can be molded into a resin molded product in the same way as the pellets and flakes of the present disclosure containing the thermoplastic starch composition of the present disclosure.

[0058] The difference (Z0-Z) between the breaking elongation change rate Z of the compound body of the present disclosure and the breaking elongation change rate Z0 of the compound body produced from the thermoplastic starch composition not containing the metal halide salt may be, for example, a lower limit of 3% or more, 5% or more, 8% or more, 9% or more, 10% or more, 15% or more, or 20% or more. Note that the larger the difference, the better the physical properties of the compound body, so the upper limit of the difference is not particularly limited. Note that the breaking elongation change rates Z and Z0 are calculated by the following formulas (3-1) and (3-2). Z = {(C-D) / C} × 100 (3-1) Z o ={(CD o ) / C}×100 (3-2) In the formula (3-1) and the formula (3-2), C is the breaking elongation of the other thermoplastic resin before being blended into the thermoplastic starch composition, D is the breaking elongation of a compound body containing the thermoplastic starch composition containing the metal halide salt and the other thermoplastic resin, D0 is the breaking elongation of a compound body containing the thermoplastic starch composition not containing a metal halide salt and the other thermoplastic resin.

[0059] The breaking elongation can be measured by the method described in the examples below.

[0060] As described above, the molded resin product of the present disclosure includes the thermoplastic starch composition of the present disclosure. The molded resin product of the present disclosure may further include the compound body, for example.

[0061] <Method for producing thermoplastic starch composition, method for producing pellets, flakes, etc., and method for producing compound body> Next, a method for producing the thermoplastic starch composition of the present disclosure, a method for producing pellets, flakes, etc., and a method for producing a compound body will be described.

[0062] [Method of producing thermoplastic starch composition] As described above, the method for producing the thermoplastic starch composition of the present disclosure includes a mixing step of mixing raw materials containing the starch, the starch plasticizer, and the metal halide salt. The raw materials may also contain, for example, the other additives in the thermoplastic starch composition of the present disclosure.

[0063] The mixing step will be specifically described with an example. In the mixing step, for example, the starch, the starch plasticizer, and the metal halide salt are kneaded while being heated. By the kneading, the thermoplastic starch composition of the present disclosure is obtained. Examples of equipment for the kneading include a mill, a despa, a mixer kneader, a Banbury mixer, a roll, a single-screw or multi-screw extruder having two or more screws, a continuous kneader, and the like. In addition, a plurality of these kneaders may be combined, for example, a 1.5-screw extruder that combines a single screw and a twin screw extruder. In the present disclosure, there is no particular limitation, but for example, a multi-screw extruder and a combination thereof are preferred from the viewpoint of production speed, and a twin screw extruder is more preferred.

[0064] The pressure during the kneading is not particularly limited, but from the viewpoint of stable production, for example, it is 0 MPa or more and 15 MPa or less, 10 MPa or less, 5 MPa or less, or 3 MPa or less, and the range is, for example, preferably 0 to 15 MPa, 0 to 10 MPa, or 0 to 5 MPa, and more preferably 0 to 3 MPa.

[0065] The temperature during the kneading is not particularly limited, but is, for example, 80°C or more, 90°C or more, or 100°C or more from the viewpoint of sufficiently plasticizing the starch, and is 300°C or less, 250°C or less, or 200°C or less from the viewpoint of preventing carbonization of the starch, and the range is, for example, 80 to 300°C, 90 to 250°C, or 100 to 200°C.

[0066] In the mixing step, the order of mixing is not particularly limited as long as the starch is plasticized and the thermoplastic starch composition of the present disclosure can be obtained. For example, the starch, the starch plasticizer, and the metal halide salt may all be introduced into the kneading equipment at the same time, or the starch and the metal halide salt may be mixed first, and then the starch plasticizer may be further mixed and introduced into the kneading equipment.

[0067] The method for mixing the metal halide salt with the starch is not particularly limited, and for example, the metal halide salt may be mixed with the starch in advance, or may be mixed simultaneously with the starch plasticizer. The metal halide salt may be added from a raw material inlet separate from the starch, using an extruder or the like. From the viewpoint of dispersibility in the raw materials contained in the thermoplastic starch composition, the metal halide salt is preferably mixed simultaneously with the starch plasticizer, and more preferably mixed in advance.

[0068] The metal halide salt may be mixed as a solid, such as a powder, or as a liquid, such as an aqueous solution, from the viewpoint of dispersion.

[0069] [Manufacturing methods for pellets, flakes, etc.] After the kneading, for example, the thermoplastic starch composition discharged from a heated discharge portion may be molded into an appropriate shape. The shape after molding is not particularly limited, and examples thereof include pellets, flakes, crumbs, powder, sheets, and chips. After kneading, the composition may be directly molded into a molded product. In this specification, molded products in the form of pellets, flakes, or sheets may be simply referred to as "pellets," "flakes," or "sheets."

[0070] In the case of forming the pellets or flakes, the pellets or flakes of the present disclosure can be produced, for example, as follows: As described above, the method for producing the pellets or flakes of the present disclosure includes a strand forming step of extruding the thermoplastic starch composition of the present disclosure to form strands, and a strand cutting step of cutting the strands to form pellets or flakes.

[0071] The strand formation step includes, for example, a step of extruding the thermoplastic starch composition mixed in the mixing step (extrusion step). The extrusion step can be performed, for example, using a conventionally known extruder. The extruder is not particularly limited, but for example, a twin-screw extruder can be used. Both the mixing step and the extrusion step may be performed by an extruder. The composition obtained in the mixing step may be recovered and supplied to the extruder in the extrusion step to form strands.

[0072] The strand cutting step is, for example, a step of cutting the thermoplastic starch composition in the form of a strand discharged from an extrusion outlet in the extrusion step. Methods for making the thermoplastic starch composition in the form of a strand into pellets or flakes include, for example, a cold cut method in which the strand is air- or water-cooled and then cut with a strand cutter, a hot cut method in which the strand is cut with a rotary cutter attached to the outlet of an extruder, an underwater cut method, and the like. For example, from the viewpoint of quality stability, the cold cut method and the hot cut method are preferred, and the cold cut method is more preferred.

[0073] [Compound body manufacturing method] As described above, the method for producing the compound body of the present disclosure includes a first kneading step of kneading a raw material containing the pellets or flakes of the present disclosure with the thermoplastic resin. The raw material may contain, for example, other thermoplastic resins, the other additives, etc.

[0074] [Method of manufacturing resin molded products] As described above, the method for producing a resin molded product of the present disclosure includes a resin molding step of producing a resin molded product by resin molding a raw material containing the compound body of the present disclosure. The resin molding step may include, for example, a second kneading step of kneading the compound body of the present disclosure with a raw material containing another thermoplastic resin, and a resin molding step of resin molding the kneaded product obtained in the second kneading step.

[0075] The resin molding step may be, for example, a step of resin molding the compound obtained in the first kneading step to produce a resin molded product. The resin molding step may be, for example, a conventionally known method. Examples of the method include calendar molding, thermoforming, extrusion blow molding, inflation molding, vacuum molding, cast molding, foam molding, extrusion molding, injection molding, press molding, and melt spinning. Examples of the molded products include containers, packaging materials, cushioning materials, daily necessities, machine parts, building materials, and automobile parts. EXAMPLES

[0076] Next, examples of the present disclosure will be described, but the present disclosure is not limited to the following examples.

[0077] In this Example and the above-described embodiment, the melt flow rate (MFR), water content, breaking elongation, and whiteness of the thermoplastic starch composition were measured by the following procedures.

[0078] [MFR measurement] The MFR was measured in accordance with JIS K 7210 using a melt indexer (Toyo Seiki Co., Ltd., product name: G-02) at a temperature of 160°C and a load of 5 kg. The measurement sample was prepared by weighing out 30 g of a pellet-shaped thermoplastic starch composition onto an aluminum tray, spreading the pellets out so as not to overlap, heating them at 160°C for 30 minutes, and then leaving them to cool at room temperature for 6 hours. The heat treatment was performed using a shelf-type air blower dryer (Advantec Toyo Co., Ltd., product name: DRK632DC).

[0079] [Moisture content] The moisture content of the starch was measured by the dry weight method using a moisture meter (Brabender, product name: MT-C) at 130° C. for 20 minutes.

[0080] The moisture content in the raw materials was calculated from the moisture contained in the starch, thermoplastic resin, elastomer, and other additives including the emulsifier used in the raw materials and the composition ratio (weight ratio used) of each raw material. In this example, the moisture content in the raw materials was calculated using a moisture meter, but the moisture content of the thermoplastic resin, elastomer, and other additives including the emulsifier may be measured by the Karl Fischer method.

[0081] The total moisture content of the raw materials was calculated from the ratio of the sum of the weight of water added to the thermoplastic starch composition and the moisture content of the raw materials obtained by the above method to the total weight of the thermoplastic starch composition.

[0082] [Elongation at break] The compound body obtained by the method described below was sandwiched between PET films and molded at 150°C and 0.8t for 6 minutes using a heat press machine (As One Corporation, product name: H300-1), and the PET film was removed and cooled to room temperature to produce a film with a thickness of 0.1 to 1.5 mm. The obtained film was left to stand at 23°C and 50% RH for one day, and then molded into a dumbbell test piece (JIS K 7127 Type 5) using a lever-type sample cutter (Dumbbell Corporation, model number: SDL-100). Nine samples of the prepared dumbbell test pieces were measured in an environment of 23°C and 50% RH using a universal material testing machine (A&D Corporation, model number: RTG-1210) with a chuck distance of 70 mm and a tensile speed of 100 mm / min, and the tensile elongation at break (break elongation) was measured. The break elongation was calculated as the average value of 7 samples excluding the maximum and minimum values ​​from the measurement results of the 9 samples. Unless otherwise specified, the breaking elongation (%GL) defined in this specification is the result obtained by the above method. The result obtained by the above method is defined as the characteristic of the thermoplastic starch composition in this example.

[0083] In addition, the breaking elongation change rates Z and Z0 were calculated according to the formulas (3-1) and (3-2) described in the embodiment, and the difference (Z0-Z) was calculated from the calculated breaking elongation change rates Z and Z0.

[0084] [Whiteness] The thermoplastic starch composition obtained by the method described below or the compound body obtained by the method described below was analyzed for whiteness (WB) in accordance with JIS Z8715 using a color difference meter (Nippon Denshoku Industries Co., Ltd., product name: SE7700). Unless otherwise specified, the whiteness (WB) defined in this specification is the result obtained by the above method, and the result obtained by the above method is defined as the characteristic of the thermoplastic starch composition in this example. The whiteness change rate was calculated by the above formula (1) explained in the embodiment. In addition, heating at 160°C for 30 minutes was performed using a shelf-type air dryer (Advantec Toyo Co., Ltd., product name: DRK632DC).

[0085] Based on the calculated whiteness change rate, the whiteness change rate of the comparative example (thermoplastic starch composition not containing a metal halide salt) was calculated as X a The whiteness change rate of the example (the thermoplastic starch composition in which a part of the starch plasticizer contained in the thermoplastic starch composition of the comparative example is replaced with a metal halide salt) is X b The difference in the whiteness change rate (X a -X b ) was calculated.

[0086] <Production of Thermoplastic Starch Composition> (Materials used) In this example, the starches used were "unmodified corn starch (Nihon Shokuhin Kako Co., Ltd., product name: Nisshoku Corn Starch Y (moisture content 13.2%)"), "unmodified tapioca starch (Asia Modified Starch Co., Ltd., product name: TAPIOCA STARCH (moisture content 13.2%)"), and "modified tapioca starch (Nihon Shokuhin Kako Co., Ltd., product name: Nisshoku Clear Text B-3 (moisture content 12.3%))". In this comparative example, the oxidized starch used was "oxidized starch (Nihon Shokuhin Kako Co., Ltd., product name: MS#3800 (moisture content 13.9%)". The starch content listed in the table includes the moisture content of the starch. In this example, "corn starch" may be simply referred to as "constarch".

[0087] "Glycerin (Kanto Chemical Co., Ltd.)" and "sorbitol (Kanto Chemical Co., Ltd.)" were used as starch plasticizers.

[0088] The metal halide salts used were magnesium chloride hexahydrate (Kanto Chemical Co., Ltd., special grade), calcium chloride (Kanto Chemical Co., Ltd., special grade), and magnesium bromide hexahydrate (Fujifilm Wako Pure Chemical Industries, Ltd.).

[0089] [Example 1, Comparative Example 1] Pellets containing the thermoplastic starch compositions of this example and comparative example were made by the following procedure.

[0090] (Production of pellets containing thermoplastic starch composition) The raw materials shown in Table 1 below were mixed in advance in a Kenwood mixer. The obtained mixture was fed from a feeder installed on the top of C1 (the inlet of the kneader) of a twin-screw extruder (φ20 mm, L / D=45, Technobel Corporation). In this embodiment, pellets were produced using a twin-screw extruder, but the device for producing the pellets is not limited to this. The kneading temperature was adjusted so that the outlet product temperature (the temperature of the thermoplastic starch composition at the outlet of the kneader) was 128°C, and the shaft rotation speed was set to 100 rpm. The discharged strand was air-cooled on a belt conveyor (Shinsei Sangyo Co., Ltd., model: SMB-100) and fed to the inlet of a pelletizer (Technobel Corporation, product name: SCP-203-2MT). The strand pulled by the pelletizer was cut in the pelletizer to produce pellets containing the thermoplastic starch compositions of Example 1 and Comparative Example 1 shown in Table 1 below (Test Areas A-1 to 10, 12, and X-1 to 7).

[0091] The pellets containing the thermoplastic starch composition of test area A-11 were produced by the following method. In test area A-11, metal halide salt-treated starch was used as a raw material. The method for preparing the metal halide salt-treated starch was to first dissolve 1% by weight of the metal halide salt relative to the weight of the starch in 20% by weight of water relative to the weight of the starch. Next, the dissolved material was mixed with starch (unprocessed corn starch), dried at 130°C for 1 hour, and cooled at room temperature to obtain a metal halide salt-treated starch. Thereafter, the obtained metal halide salt-treated starch and each raw material were premixed in advance without adding any new metal halide salt so that the raw material composition and total raw material moisture content in Table 1 were obtained, and the mixture after the mixing was supplied from a feeder installed at the top of C1 of the twin-screw extruder. After supplying from the feeder, the same operation as in test area A-1 was performed to produce pellets containing the thermoplastic starch composition of test area A-11.

[0092] In addition, for test plot A-13, the same operation as in test plot A-1 was carried out except that the kneading temperature was changed to 173°C at the outlet of the test plot, instead of the kneading temperature in test plot A-1, etc., to produce pellets containing the thermoplastic starch composition of test plot A-13.

[0093] For reference, FIG. 1 shows photographs of the thermoplastic starch compositions of test plots A-2, X-1, and X-2 before and after heating.

[0094] [Table 1-1]

[0095] [Table 1-2]

[0096] [Table 1-3]

[0097] [Example 2, Comparative Example 2] The compound bodies of the present example and the comparative example were prepared according to the following procedure.

[0098] (Production of compound body containing thermoplastic starch composition) The thermoplastic starch composition prepared in Example 1 and Comparative Example 1, a thermoplastic resin (LDPE, Tosoh Corporation, product name: Petrothene (registered trademark) LDPE183, MFR 2g / 10min (according to JIS K 6922-1), breaking elongation 400.3%GL), and a compatibilizer (Mitsui Chemicals, Inc., product name: Admer HE-810) were placed in a polyethylene bag, the mouth of the bag was tied, and the bag was shaken up and down and left and right to mix well. The entire amount was supplied from a feeder installed at the top of C1 of a twin-screw extruder (φ20mm, L / D=45, Technovel Co., Ltd.). The kneading temperature was adjusted so that the outlet product temperature was 159°C, and the shaft rotation speed was set to 150 rpm. The discharged strand compound body was held by hand, water-cooled in a water tank (Technovel Co., Ltd., product name: SCB150-1500), and supplied to the inlet of a pelletizer (Technovel Co., Ltd., product name: SCP-203-2MT). The strand pulled by the pelletizer was cut in the pelletizer to produce a pellet-shaped compound body. The breaking elongation (%GL) and whiteness (WB) of the obtained compound body were measured.

[0099] [Table 2-1]

[0100] [Table 2-2]

[0101] [Table 2-3]

[0102] [Example 3, Comparative Example 3] In the present examples and comparative examples, compound bodies were prepared using thermoplastic resins having different fluidities.

[0103] The compound bodies of Example 3 and Comparative Example 3 were produced in the same manner as in Example 2, except that the thermoplastic resin was changed to a thermoplastic resin with different fluidity as shown in Table 3 below (LDPE, Tosoh Corporation, product name: Petrothene (registered trademark) LDPE212, MFR 13 g / 10 min (according to JIS K 6922-1), breaking elongation 317.3% GL; LDPE, Tosoh Corporation, product name: Petrothene (registered trademark) LDPE249, MFR 70 g / 10 min (according to JIS K 6922-1), breaking elongation 287.5% GL).

[0104] [Table 3-1]

[0105] [Table 3-2]

[0106] [Example 4, Comparative Example 4] In the present examples and comparative examples, the type of thermoplastic resin was changed to polypropylene (PP) to prepare the compound body.

[0107] The compound bodies of Example 4 and Comparative Example 4 were produced in the same manner as in Example 2, except that the thermoplastic resin was changed to the thermoplastic resin shown in Table 4 below (PP, Sunallomer Co., Ltd., product name: PF621S, MFR 6.5 g / 10 min (according to JIS K 6921-2), breaking elongation 584.4% GL; PP, Japan Polypropylene Corporation, product name: MG03BD, MFR 30 g / 10 min (according to JIS K 7210), breaking elongation 165.3% GL) and the set temperature of each die of the twin-screw extruder was adjusted so that the outlet product temperature was 180°C.

[0108] [Table 4]

[0109] [Example 5, Comparative Example 5] In the present examples and comparative examples, the compound bodies were produced by changing the type of thermoplastic resin.

[0110] The compounds of Example 5 and Comparative Example 5 were produced in the same manner as in Example 2, except that the thermoplastic resin was changed to the thermoplastic resin shown in Table 5 below (PBS, Mitsubishi Chemical Corporation, product name: FZ91, MFR 5 g / 10 min (according to ISO 1133), elongation at break 52.9% GL).

[0111] [Table 5]

[0112] [Example 6, Comparative Example 6] In the present examples and comparative examples, compound bodies were prepared by changing the blending ratio of thermoplastic resins.

[0113] Compound bodies of Example 6 and Comparative Example 6 were produced in the same manner as in Example 2, except that the blending ratios of the thermoplastic starch composition and the thermoplastic resin were changed as shown in Table 6 below.

[0114] [Table 6]

[0115] As shown in Table 1, all of the thermoplastic starch compositions containing a metal halide salt in Example 1 were found to have fluidity. In addition, the whiteness change rate was smaller than that of the thermoplastic starch composition in Comparative Example 1 containing no metal halide salt. In other words, it was confirmed that both fluidity and high whiteness were achieved (Tests A-1 to A-13).

[0116] On the other hand, the thermoplastic starch composition of Comparative Example 1, which did not contain a metal halide salt, had a larger whiteness change rate than the thermoplastic starch composition of Example 1, which contained a metal halide salt. That is, it was more susceptible to coloring by heating than Example 1 (Test Plots X-1 and X-2). Furthermore, Test Plots X-1 and X-3, which contained corn starch, an unprocessed starch, showed no fluidity at all, and MFR could not be measured. Furthermore, Test Plot X-2, which used oxidized starch that had been reduced in molecular weight by oxidation treatment, had a high MFR, but a very high whiteness change rate of 90% or more.

[0117] As shown in Table 2, the test plots of the Examples had higher whiteness than the Comparative Examples under conditions where the thermoplastic starch composition was blended with glycerol or sorbitol as a starch plasticizer, and LDPE183 was blended as a thermoplastic resin (test plots B1-1A to B1-5B). In addition, the breaking elongation change rate Z of the Examples was all smaller than the breaking elongation change rate Z0 of the Comparative Examples. In other words, the Examples had less change in breaking elongation from the raw material LDPE183 compared to the Comparative Examples.

[0118] On the other hand, the test plots of the comparative examples all had lower whiteness than the test plots of the examples (test plots B1X-1A to B1X-2B). In addition, the test plots B1X-2A and B1X-2B all showed low values ​​of the breaking elongation change rate as low as the examples, but the whiteness (WB) was significantly low at 30 or less. This result suggests that the properties of the thermoplastic starch composition (X-2), which is the raw material of the compound body, are significantly affected. The above-mentioned tendency was the same regardless of the presence or absence of the compatibilizer.

[0119] As shown in Table 3, even when the thermoplastic resin was changed to another PE with different fluidity, the Examples (Tests B2-1 to B2-5) were superior to the Comparative Examples (Tests B2X-1 to B2X-6) in both whiteness (WB) and rate of change in elongation at break. Note that the Comparative Example (Test B2X-4) showed a lower rate of change in elongation at break than the Examples, but the whiteness (WB) was lower than the Examples.

[0120] As shown in Table 4, even when the thermoplastic resin was changed to PP, the examples (test plots B3-1 to B3-2) were superior to the comparative examples (test plots B3X-1 to B3X-4) in both whiteness (WB) and rate of change in elongation at break.

[0121] As shown in Table 5, even when the thermoplastic resin was changed to PBS, the example (test group B4-1) was superior to the comparative examples (test groups B4X-1 to B4X-2) in both whiteness (WB) and rate of change in elongation at break.

[0122] As shown in Table 6, even with a high content of the thermoplastic starch composition, the Example (Test Plot B5-1) was superior in both whiteness (WB) and breaking elongation to the Comparative Examples (Test Plots B5X-1 to B5X-2) which also had a high content of the thermoplastic starch composition. Note that the Comparative Example (Test Plot B5X-2) showed a lower breaking elongation change rate than the Examples, but a lower whiteness (WB) than the Examples.

[0123] <Additional Notes> A part or all of the above-described embodiments and examples may be described as follows, but is not limited to the following. (Appendix 1) 1. A thermoplastic starch composition comprising: The present invention comprises a starch, a plasticizer for starch, and a metal halide salt, The thermoplastic starch composition has a melt flow rate of 0.01 g / 10 min or more at a temperature of 160 ° C. and a load of 5 kg according to JIS K 7210. Thermoplastic starch composition. (Appendix 2) 2. The thermoplastic starch composition of claim 1, wherein the starch is a non-oxidized starch. (Appendix 3) The total weight of all components other than water contained in the thermoplastic starch composition is taken as 100% by weight, The starch content is 55 to 85% by weight, The content of the starch plasticizer is 10 to 40% by weight, The content of the metal halide salt is 0.1 to 10% by weight. 3. The thermoplastic starch composition according to claim 1 or 2. (Appendix 4) 4. The thermoplastic starch composition according to any one of claims 1 to 3, wherein the thermoplastic starch composition formed into pellets has a whiteness change rate X of 40% or less, calculated by the following formula (1): X = {(AB) / A} × 100 (1) In the formula (1), A is the whiteness (WB) of the thermoplastic starch composition after molding, calculated in accordance with JIS Z8715; B is the whiteness (WB) of the thermoplastic starch composition after the molding is heated at 160° C. for 30 minutes, calculated in accordance with JIS Z8715. (Appendix 5) The thermoplastic starch composition according to any one of claims 1 to 4, comprising at least one of polyhydric alcohols and sugars as the starch plasticizer. (Appendix 6) The polyhydric alcohol is at least one selected from the group consisting of glycerin, propylene glycol, and ethylene glycol, The saccharide is at least one of sorbitol and glucose. 6. The thermoplastic starch composition of claim 5. (Appendix 7) 7. The thermoplastic starch composition according to any one of claims 1 to 6, wherein the thermoplastic starch composition is substantially free of water as a plasticizer for starch. (Appendix 8) The thermoplastic starch composition according to any one of claims 1 to 7, wherein the metal halide salt comprises at least one selected from the group consisting of metal chloride salts, metal bromide salts, and metal iodide salts. (Appendix 9) 9. The thermoplastic starch composition according to any one of claims 1 to 8, wherein the metal halide salt comprises a metal chloride salt. (Appendix 10) 9. The thermoplastic starch composition according to any one of claims 1 to 8, wherein the metal halide salt is at least one selected from the group consisting of sodium chloride, magnesium chloride, calcium chloride, aluminum chloride, sodium bromide, magnesium bromide, calcium bromide, sodium iodide, magnesium iodide, and calcium iodide. (Appendix 11) 1. A thermoplastic starch composition comprising: The present invention comprises a starch, a plasticizer for starch, and a metal halide salt, A thermoplastic starch composition, wherein the thermoplastic starch composition formed into pellets has a whiteness change rate X of 40% or less, as calculated by the following formula (1): X = {(AB) / A} × 100 (1) In the formula (1), A is the whiteness (WB) of the thermoplastic starch composition after molding, calculated in accordance with JIS Z8715; B is the whiteness (WB) of the thermoplastic starch composition after the molding is heated at 160° C. for 30 minutes, calculated in accordance with JIS Z8715. (Appendix 12) 12. A pellet comprising the thermoplastic starch composition of any of claims 1 to 11. (Appendix 13) 12. A flake comprising the thermoplastic starch composition of any one of claims 1 to 11. (Appendix 14) 12. A compound body comprising the thermoplastic starch composition according to any one of claims 1 to 11. (Appendix 15) A resin molded article comprising the thermoplastic starch composition according to any one of claims 1 to 11. (Appendix 16) A mixing step of mixing raw materials containing the starch, the starch plasticizer, and the metal halide salt, 12. A method for producing a thermoplastic starch composition according to any one of claims 1 to 11. (Appendix 17) a strand forming step of extruding the thermoplastic starch composition to form strands; and a strand cutting step of cutting the strands to form pellets or flakes, 12. A method for producing pellets or flakes, wherein the thermoplastic starch composition is a thermoplastic starch composition according to any one of claims 1 to 11. (Appendix 18) A first kneading step of kneading a raw material containing pellets or flakes and a raw material containing a thermoplastic resin, The pellet is as described in appended claim 12, The method for producing a compound body, wherein the flakes are the flakes described in Appendix 13. (Appendix 19) A resin molding process is included in which a raw material including a compound body is resin-molded to produce a resin molded product, The compound body is the compound body described in Appendix 14. (Appendix 20) A second kneading step of kneading the compound body with a raw material containing another thermoplastic resin; A resin molding step of producing a resin molded product by resin molding the kneaded product obtained in the second kneading step. A method for producing a resin molded product according to claim 19. [Industrial Applicability]

[0124] As described above, the present disclosure can provide a thermoplastic starch composition, pellets, flakes, compound body, resin molding, a method for producing a thermoplastic starch composition, a method for producing a pellet or flake, a method for producing a compound body, and a method for producing a resin molding, which are less colored and have fluidity. The present disclosure can provide, for example, a thermoplastic starch composition and a master batch of a thermoplastic starch composition, which are less colored and have fluidity. In addition, for example, by kneading the thermoplastic starch composition of the present disclosure with a thermoplastic resin, a compound body with a high starch content can be efficiently mass-produced. For example, by supplying a thermoplastic starch composition with high fluidity, i.e., a high MFR, a compound body is provided that exhibits good physical properties different from those of a kneaded product with a conventional thermoplastic starch composition having a low MFR, for example, a compound body exhibiting a high breaking elongation value is provided. The use of the present disclosure is not particularly limited. For example, the use of the thermoplastic starch composition of the present disclosure is not limited to the pellets, flakes, and resin molding of the present disclosure, but is optional, and can be used in a wide range of applications.

Claims

1. 1. A thermoplastic starch composition comprising: The present invention comprises a starch, a plasticizer for starch, and a metal halide salt, The thermoplastic starch composition has a melt flow rate of 0.01 g / 10 min or more at a temperature of 160° C. and a load of 5 kg according to JIS K 7210. Thermoplastic starch composition.

2. The thermoplastic starch composition of claim 1 , wherein the starch is a non-oxidized starch.

3. The total weight of all components other than water contained in the thermoplastic starch composition is taken as 100% by weight, The starch content is 55 to 85% by weight, The content of the starch plasticizer is 10 to 40% by weight, The content of the metal halide salt is 0.1 to 10% by weight. The thermoplastic starch composition of claim 1.

4. 2. The thermoplastic starch composition according to claim 1, wherein the thermoplastic starch composition formed into pellets has a whiteness change rate X of 40% or less, calculated by the following formula (1): X={(AB) / A}×100 (1) In the formula (1), A is the whiteness (WB) of the thermoplastic starch composition after molding, calculated in accordance with JIS Z8715; B is the whiteness (WB) of the thermoplastic starch composition after heating the molded thermoplastic starch composition at 160° C. for 30 minutes, calculated in accordance with JIS Z8715.

5. The thermoplastic starch composition according to claim 1 , wherein the starch plasticizer comprises at least one of a polyhydric alcohol and a sugar.

6. The polyhydric alcohol is at least one selected from the group consisting of glycerin, propylene glycol, and ethylene glycol, The saccharide is at least one of sorbitol and glucose. The thermoplastic starch composition of claim 5.

7. 2. The thermoplastic starch composition of claim 1, which is substantially free of water as a plasticizer for the starch.

8. 2. The thermoplastic starch composition of claim 1, wherein the metal halide salt comprises at least one selected from the group consisting of metal chloride salts, metal bromide salts, and metal iodide salts.

9. The thermoplastic starch composition of claim 1 , wherein the metal halide salt comprises a metal chloride salt.

10. 2. The thermoplastic starch composition of claim 1, wherein the metal halide salt is at least one selected from the group consisting of sodium chloride, magnesium chloride, calcium chloride, aluminum chloride, sodium bromide, magnesium bromide, calcium bromide, sodium iodide, magnesium iodide, and calcium iodide.

11. 1. A thermoplastic starch composition comprising: The present invention comprises a starch, a plasticizer for starch, and a metal halide salt, A thermoplastic starch composition, wherein the thermoplastic starch composition formed into pellets has a whiteness change rate X of 40% or less, as calculated by the following formula (1): X={(AB) / A}×100 (1) In the formula (1), A is the whiteness (WB) of the thermoplastic starch composition after molding, calculated in accordance with JIS Z8715; B is the whiteness (WB) of the thermoplastic starch composition after heating the molded thermoplastic starch composition at 160° C. for 30 minutes, calculated in accordance with JIS Z8715.

12. A pellet comprising the thermoplastic starch composition of any one of claims 1 to 11.

13. A flake comprising the thermoplastic starch composition of any one of claims 1 to 11.

14. A compounded body comprising the thermoplastic starch composition according to any one of claims 1 to 11.

15. A resin molded article comprising the thermoplastic starch composition according to any one of claims 1 to 11.

16. A mixing step of mixing raw materials containing the starch, the starch plasticizer, and the metal halide salt, A method for producing the thermoplastic starch composition according to any one of claims 1 to 11.

17. a strand forming step of extruding the thermoplastic starch composition to form strands; and a strand cutting step of cutting the strands to form pellets or flakes, The thermoplastic starch composition according to any one of claims 1 to 11, wherein the thermoplastic starch composition is a thermoplastic starch composition according to any one of claims 1 to 11.

18. A first kneading step of kneading a raw material containing pellets or flakes and a raw material containing a thermoplastic resin, The pellet is a pellet according to claim 12, The method for producing a compound body, wherein the flakes are the flakes according to claim 13.

19. A resin molding process is included in which a raw material including a compound body is resin-molded to produce a resin molded product, The method for producing a resin molded product, wherein the compound body is the compound body according to claim 14.

20. A second kneading step of kneading the compound body with a raw material containing another thermoplastic resin; A resin molding step of producing a resin molded product by resin molding the kneaded product obtained in the second kneading step. A method for producing the resin molded product according to claim 19.

Citation Information

Patent Citations

  • Empty capsule and soft capsule based on modified starch

    CN105997930A

  • Composition for molded dough

    CN106317469A

  • Polymer composition for production of high-frequency weldable article, master mixture for production of this composition, and produced article

    JP1994207046A

  • Biodegradable composition and molding method therefor

    JP2003105130A

  • Resin composition, film, bag product, and method for producing resin composition

    JP2011026538A